Biogas production of food waste with in-situ sulfide control under high organic loading in two-stage anaerobic digestion process: Strategy and response of microbial community. (April 2023) - Yang, Siman; Luo, Fan; Yan, Jia; Zhang, Tianlang; Xian, Ziyan; Huang, Weiyao; Zhang, Hongguo; Cao, Yongjian; Huang, Lei
Graphical abstract: Abstract: A two-stage anaerobic digestion process utilizing food waste was investigated in this study, without any additive and co-digestion. Solid content, temperature and pH value were key controlling factors for hydrolysis, which results the optimized food waste hydrolysate with COD/VSfood waste of 2.67. Efficient biogas production was maintained in long-term operation (>150 d) without any additive, and methane production yields up to 699.7 mL·gVS -1 ·d -1 was achieved under organic loading rate (OLR) of 31.0 gVS·d -1 . Methane production can be recovered (70.4 %) after temperature shock within 30 days. This study confirmed the possibility to establish two-stage food waste anaerobic digestion system under high organic load. pH, OLR, and temperature are key factors to maintain stable biogas production, while pH control was performed as a in situ sulfide control technology (75.8 % sulfide reduction). This study provides practical strategies for food waste utilization and decreasing carbon footprint.